Acute psychological responses to official match outcomes in male youth volleyball: an observational repeated-measures study within a single national-level team - Do Nascimento, M. H.; Filho, A. S. S.; Aprigliano, V.; Clemente, F. M.; Vieira, C. A.; Campos, M. H.; Rocha, A. C. R.; Arantes, D. D. L. C.; Pedrosa, G. F.; Noll, M.; Kawczynski, A.; Laporta, L.; et al. (Frontiers in Psychology, 2026)
Background: Official match outcomes may be associated with acute psychological responses in youth athletes, particularly in team sports characterized by high emotional and interpersonal demands.